2006
DOI: 10.1189/jlb.0206095
|View full text |Cite
|
Sign up to set email alerts
|

Development and function of naturally occurring CD4+CD25+ regulatory T cells

Abstract: The immune system has evolved numerous mechanisms of peripheral T cell immunoregulation, including a network of regulatory T (Treg) cells, to modulate and down-regulate immune responses at various times and locations and in various inflammatory circumstances. Amongst these, naturally occurring CD4(+)CD25(+) Treg cells (nTreg) represent a major lymphocyte population engaged in the dominant control of self-reactive T responses and maintaining tolerance in several models of autoimmunity. CD4(+)CD25(+) Treg cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 116 publications
6
69
0
1
Order By: Relevance
“…38,39 CD25, an interleukin-2 receptor, is reported to be an inflammation marker on CD4 + lymphocytes. 18 In the EIU experiment, we observed expansion of CD4 + CD25 + cells, which is consistent with the report by Toda et al 19 A significant increase in the number of CD4 + CD25 + cells was observed in both the rAAV-Venus and the rAAV-ChR2V rats at 1 week after the injections compared with the pre-injection values (Figure 8b), although there was no significant difference in the results between the rAAV-Venus and the rAAV-ChR2V injections. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…38,39 CD25, an interleukin-2 receptor, is reported to be an inflammation marker on CD4 + lymphocytes. 18 In the EIU experiment, we observed expansion of CD4 + CD25 + cells, which is consistent with the report by Toda et al 19 A significant increase in the number of CD4 + CD25 + cells was observed in both the rAAV-Venus and the rAAV-ChR2V rats at 1 week after the injections compared with the pre-injection values (Figure 8b), although there was no significant difference in the results between the rAAV-Venus and the rAAV-ChR2V injections. …”
Section: Discussionsupporting
confidence: 92%
“…There was no significant difference in the inflammation status between the rAAV injections. As a positive control of inflammation, EIU also increased the population of CD4 + CD25 + cells, which is consistent with a report by Toda et al 19 …”
supporting
confidence: 92%
“…It is generally viewed that Treg cells interact with other cells through cell-cell contact or short-range interactions to mediate their effects (23)(24)(25). To explain discrepancies (in the number of NK cells and function of NK precursors) between the spleen and LNs, we therefore evaluated the propitiousness of the environments of the LN and the spleen to short-range interactions between Treg cells and NK lineage cells.…”
Section: Nk Cells Are Located Mostly In the T Cell Zones In The Lns Bmentioning
confidence: 99%
“…CD25 is constitutively expressed at high levels on CD4 + Foxp3 + regulatory T cells (Tregs), which suppress putatively autoreactive peripheral T cells that escape thymic deletion during the establishment of central tolerance [74][75][76][77], and Treg depletion causes autoimmunity in mouse models [78]. Foxp3 is a transcription factor that is fundamental for Treg production and function [79][80][81]: Targeted ablation of the Foxp3 gene results in severe autoimmune manifestations in mice, and in humans, natural mutations of the orthologous gene lead to immune dysregulation, polyendocrinopathy, enteropathy, and Xlinked inheritance (IPEX) syndrome [82][83][84] and X-linked autoimmunity-allergic dysregulation syndrome [85].…”
Section: The Il-2/il-2r Pathway and T Cell Functionmentioning
confidence: 99%